HEALTH TECHNOLOGY ASSESSMENT IN EVALUATION OF PHARMACEUTICALS IN THE CZECH REPUBLIC - Vostalová, Lenka; Mazelová, Jana; Samek, Jiří; Vocelka, Milan (International journal of technology assessment in health care, 2017)
OBJECTIVES: In the Czech Republic, the health technology assessment (HTA) approaches have been implemented in evaluation of medicinal products since 2008. The aim of this study was to provide an overview of the implementation of HTA and different levels thereof in the evaluation process conducted by the State Institute for Drug Control (SUKL) and to describe the impact of HTA on the entrance of new medicinal entities into out-patient healthcare system including highly innovative and orphan drugs. METHODS: Materials supporting this overview were collected using the records in the database of administrative proceedings of SUKL, in-house standard operating procedures, and the legislation in force. Based on these sources as well as the hands-on knowledge of the current practice, a brief description of the general rules of administrative proceedings involving HTA of varying complexity was elaborated. Characteristic features of the individual types of proceedings, basic differences in the complexity of HTA employed, and its most important challenges were summarized. RESULTS: In Czech Republic, HTA in the formal administrative proceedings ensures a transparent process of introduction of new medicinal products into clinical practice and leaves space for restriction of reimbursement conditions to minimize budget impact. CONCLUSIONS: As a robust as well as pragmatic HTA methodology has been implemented by SUKL, relevant stakeholders (marketing authorization holders, Health Care Funds, clinical expert groups) are now able to influence reimbursement of new technologies.
Keywords: Health technology assessment; léky na předpis; Off-Label Use; Orphan Drug Production; analýza nákladů a výnosů; Administrative proceedings; Prescription Drugs; Humans; Technology Assessment, Biomedical; kontrola léčiv a omamných látek; Česká republika; Czech Republic; Orphan medicinal product; Delivery of Health Care; úhrada zdravotního pojištění; výroba orphan drugs; off-label použití léčivého přípravku; Cost-Benefit Analysis; Insurance, Health, Reimbursement; Highly innovative medicinal product; poskytování zdravotní péče; Reimbursement; hodnocení biomedicínských technologií; lidé; Drug and Narcotic Control